A cross-sectional study on co-infection of hepatitis B and hepatitis C among people living with HIV/AIDS from a tertiary care hospital of Central India - Riddhi Pradhan; Kirti Hemwani; Vidit Khandelwal; Bamboriya BL; Yogyata Marothi; Varsha Saxena (Asian Journal of Medical Sciences, 2023)
Background: Hepatitis B virus (HBV), hepatitis C virus (HCV), and Human immunodeficiency virus (HIV) infections are prevalent throughout the world. HIV infection increases the risk of HBV and HCV liver disease especially when HIV-associated immunodeficiency progresses.